Metformin Associated Lactic Acidosis without Organ Dysfunction and Effective Treatment - Mustafa Yaprak; Feyyaz Bay; Müge Özsan; İ hsan Üstün; Faruk Turgut (Archives of Renal Diseases and Management - Peertechz Publications, 2016)
Metformin is an oral antidiabetic from biguanide class and is  the  first-line  treatment  option  for  type  2  diabetes  mellitus (DM)  [1].  Most  common  side  effects  of  metformin  include gastrointestinal system side effects such as abdominal cramp, diarrhea, nausea and vomiting [2]. Lactic acidosis is a rare but fatal serious side effect of metformin and its incidence is found 9  in  every  100.000  patient  years  [3].  Nevertheless,  this  side effect  generally  occurs  in  those  who  have  organ  dysfunction (kidney, liver, lung or heart dysfunction etc.) [3,4]. In general, it is not expected in those who have no organ dysfunction. In this article, a case of severe lactic acidosis due to metformin in a patient with type 2 DM  without  any  organ  dysfunction  was presented.